Optimal dispersed generation placement in radial distribution systems using a pattern of load flow procedure – clustering optimisation - Popova, Angela (JET on-line, 2023)
Nowadays, distributed generation plays a vital role in distribution systems. It makes an indisputable contribution towards power loss minimisation and voltage profile improvement. To maximise the benefits of distributed generators, their location and size is of crucial importance. This paper describes the use of clustering optimisation (CO) as a highly effective method for determining the optimal placement and sizing of distributed generators. Assessment of the effectiveness from the clustering optimisation method is achieved by its demonstration on a 69-bus and 119-bus distribution systems. Furthermore, the results obtained from implementation of the proposed approach are compared to results from recent studies including analytical approaches, heuristic, and meta-heuristic, as well as mathematical programming algorithms. It is concluded that clustering optimisation is a simple and efficient method in terms of optimal allocation and sizing of distributed generators. It outweighs other approaches in terms of simplicity, results, and computation time.
Keywords: clustering optimisation; distribucijski sistem; distributed generation; distribution system; izgube; losses; optimizacija grozdenja; porazdeljena proizvodnja; postavitev napajanja; power injection placement